Acute Effect of Enhanced External Counterpulsation on the Carotid Hemodynamic Parameters in Patients With High Cardiovascular Risk Factors - Zhang, Yahui; Mai, Zhouming; Du, Jianhang; Zhou, Wenjuan; Wei, Wenbin; Wang, Hui; Yao, Chun; Zhang, Xinxia; Huang, Hui; Wu, Guifu (Frontiers in Physiology, 2021)
Purpose: It has not been known whether there were different hemodynamic responses in carotid arteries during and immediately after Enhanced External Counterpulsation (EECP) in patients with high cardiovascular risk factors. This study aimed to investigate the cardiovascular responses during and immediately after EECP in patients with hypertension, hyperlipidemia and type 2 diabetes. Methods: Eighty-three subjects were recruited into this study to receive 45min-EECP, including patients with hypertension (n=21), hyperlipidemia (n=23), type 2 diabetes (n=18) and healthy subjects (n=21). Hemodynamic parameters in both common carotid arteries (CCAs) were measured and calculated from Doppler ultrasound images. Peak systolic velocity (PSV), end-diastolic velocity (EDV), mean inner diameter (ID), Systolic/Diastolic flow velocity ratio (VS/VD), flow rate (FR) and resistance index (RI) were monitored before, during and immediately after 45min-EECP. Results: In patients with hypertension, there were significant changes in ID, EDV and RI immediately after EECP (all p<0.05). By contrast, in patients with type 2 diabetes, VS/VD of left (1.945±0.271 vs. 2.144±0.427, p=0.015) and right CCA (1.962±0.285 vs. 2.165±0.416, p=0.026) was just lower immediately after EECP in comparison with baselines. In patients with hyperlipidemia and healthy subjects, FR was significantly increased during EECP (p<0.05). In healthy subjects, PSV of left CCA (77.997±16.346 vs. 84.29±10.339cm/s, p=0.048) and right CCA (71.217±16.056 vs. 78.203±16.234 cm/s, p=0.023) was significantly decreased immediately after EECP. Conclusions: EECP creates different hemodynamic responses in patients with hypertension, hyperlipidemia, type 2 diabetes and healthy subjects. Blood flow velocity, vascular resistance and inner diameters are improved by EECP in patients with hypertension. EECP mainly increases inner diameters and blood flow in patients with hyperlipidemia. Additionally, blood flow velocity is decreased by EECP in patients with type 2 diabetes.